THE EFFECT OF TREKKING SPORT TOURISM ON SELF-CONTROL AND COOPERATION IN NOKILALAKI MOUNTAINERS SIGI REGENCY - Didik Purwanto; Moh Rifki (Journal Physical Education, Health and Recreation, 2022)
The purpose of this study was to determine the results of the analysis of the influence of trekking sport tourism on self-control and cooperation on mountain climbers, Nokilalaki, Sigi Regency. This study uses a quantitative descriptive approach without giving special treatment to respondents, then data collection is carried out using survey methods in the form of questionnaires or question naires. Closed with the help of the media google forms whose answer is already served so that respondents can choose answers according to their respective opinions. The sample selection used a non-probability sampling technique with an accidental sampling approach that was tailored to the needs and still took into account the representation of the population. The samples used were 137 people who had done trekking on mount Nokilalaki, Sigi Regency. Data from the results of this study are grouped according to the type then analyzed using the help of the microsoft excel 2013 application. The results showed the effect of trekking sport tourism on self-control and cooperation in Nokilalaki mountain climbers, Sigi Regency with a percent age very low 7%; low 15%; moderate 49%; high 22%; very high 7%. So, it can be concluded that overall trekking activity sports tourism have a moderate influence on aspects of self-control and cooperation of Nokilalaki mountain climbers, Sigi Regency.